Pengaruh Terapi Butterfly Hug terhadap Tingkat Kecemasan dalam Penyusunan Karya Tulis Ilmiah pada Mahasiswa Keperawatan Universitas Abulyatama - Widia Santri Telaumbanua; Nurul Sakdah; Yuli Zuhkrina (Jurnal Ventilator, 2026)
Final-year students often experience anxiety while preparing their scientific papers, which can disrupt their academic performance and mental well-being. This condition commonly arises due to the pressure of completing the final assignment, academic demands, limited time, and fear of failure. One method that can be used to reduce this anxiety is the Butterfly Hug therapy. Butterfly Hug is a simple relaxation technique involving gentle alternating taps on the chest and shoulder area, aimed at stimulating the body’s relaxation response. This technique has been recognized as effective in reducing anxiety by enhancing calmness, focus, and emotional balance.The purpose of this study was to determine the effect of Butterfly Hug therapy on the anxiety levels of students during the preparation of their scientific papers. This study used a quasi-experimental design with a one-group pretest–posttest approach. The sample consisted of 15 students selected through purposive sampling based on the study criteria. Data collection was conducted using the Zung Self-Rating Anxiety Scale (Z-SAS), while the intervention was administered for three consecutive days with a duration of 10 minutes for each session. The research was carried out from June 16–20, 2025 at the Diploma III Nursing Program, Faculty of Health Sciences, Abulyatama University, Aceh Besar.Data were analyzed using the Wilcoxon test. The results showed a decrease in anxiety levels with a difference score of 3.162 points. The statistical test revealed a p-value of 0.002, indicating a significant effect of Butterfly Hug therapy on student anxiety levels (p < 0.05). These findings confirm that Butterfly Hug therapy can serve as an effective non-pharmacological intervention to help students manage academic anxiety and encourage them to apply it whenever they experience heightened stress.